Trans-anethole exerts protective effects on lipopolysaccharide-induced acute jejunal inflammation of broilers via repressing NF-κB signaling pathway - Yichun Tong; Caiyun Yu; Shun Chen; Xianglei Zhang; Zaibin Yang; Tian Wang (Poultry Science, 2023)
ABSTRACT: This study aimed to explore the effects of trans-anethole (TA) on lipopolysaccharide (LPS)-induced acute jejunal inflammation model of broilers. A total of 160 one-day-old broilers (male; Arbor Acres) were randomly allocated into four treatment groups with 8 replicates of 5 birds each. On d 20, the dose of 5 mg/kg body weight LPS solution and the equal amount of sterile saline were intraperitoneally injected into LPS-challenged and unchallenged broilers, respectively. Compared with the control group, LPS decreased (P < 0.05) the villus height (VH) and the ratio of villus height to crypt depth (VCR) but increased (P < 0.05) the crypt depth (CD), meanwhile, enhanced (P < 0.01) the levels of interleukin-6 (IL-6), interleukin-1beta (IL-1β) and tumor necrosis factor-alpha (TNF-α) but decreased (P < 0.01) the level of interleukin-10 (IL-10). The group supplemented with 600 mg/kg of TA had lower (P < 0.01) CD and higher (P < 0.01) VCR than the LPS group. TA increased (P < 0.01) the level of IL-10 and decreased (P < 0.01) the level of IL-1β. The mRNA expression levels of IL-6, nuclear factor kappa B (NF-κB), TNF-α were up-regulated (P < 0.05) and the levels of IL-10 and inhibitor of NF-κB alpha (IκBα) were down-regulated (P < 0.05) by LPS as compared with the control group. TA down-regulated (P < 0.05) the increased mRNA expression levels of genes caused by LPS, as well as up-regulated (P < 0.05) the levels of IL-10 and IκBα. Furthermore, LPS down-regulated (P < 0.05) and up-regulated (P < 0.05) the protein expression levels of IκBα and NF-κB p65, respectively. TA up-regulated (P < 0.05) the level of IκBα and down-regulated (P < 0.05) the level of NF-κB p65. The conclusion of this study is that TA could exert protective effect on the LPS-induced acute jejunal inflammation of broilers via repressing the activation of NF-κB and the 600 mg/kg is the optimal dose against LPS-induced acute jejunal inflammation of broilers.